Alcohol, Drugs, and Road Traffic Crashes in India : A Systematic Review - Das, Ashis (Taylor and Francis, 2013)
Objective: India reported the highest number of road traffic crashes, related injuries, and deaths among all countries in the world, with 105,725 road traffic fatalities and 452,922 nonfatal road traffic injuries in 2007. In this report we present a systematic review of available literature on the use of psychoactive substances (alcohol and drugs) among road users, particularly those involved in road traffic crashes (RTCs).